Tingkat Pemahaman Guru Terhadap Karakteristik Peserta Didik Pada Mata Pelajaran Tematik di MI - Hesti Prastiwi; Kanthi Pamungkas Sari; Irham Nugroho (Universitas Muhammadiyah Magelang, 2021)
The research objective was to determine the level of teacher understanding of students in thematic subjects at MI Muhammadiyah 1 Rambeanak. This research is a descriptive study with a qualitative approach. The data analysis used is in accordance with Miles and Huberman's theory. Data sources consist of primary and secondary data sources. The results showed that the teacher understood the various characteristics of each student well. Teachers can find out the characteristics of students in various ways. Recognizing the character of students will help teachers to deliver students to achieve their goals. When the teacher can understand the characteristics of each student, the teacher will be able to provide the right approach and treatment, especially in the learning process, act fairly, and can solve the problems experienced by students by paying attention to their characteristics.